2023
DOI: 10.1126/sciadv.ade1444
|View full text |Cite
|
Sign up to set email alerts
|

Ionizable lipid nanoparticles deliver mRNA to pancreatic β cells via macrophage-mediated gene transfer

Abstract: Systemic messenger RNA (mRNA) delivery to organs outside the liver, spleen, and lungs remains challenging. To overcome this issue, we hypothesized that altering nanoparticle chemistry and administration routes may enable mRNA-induced protein expression outside of the reticuloendothelial system. Here, we describe a strategy for delivering mRNA potently and specifically to the pancreas using lipid nanoparticles. Our results show that delivering lipid nanoparticles containing cationic helper lipids by intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 100 publications
1
34
0
Order By: Relevance
“…In addition to IV delivery, we considered other clinically relevant delivery routes, including intramuscular (IM) and intraperitoneal (IP) administration. Intramuscular injections are the preferred route for prophylactic RNA vaccines (29, 30), including the SARS-CoV-2 vaccines (31, 32), while intraperitoneal injections are commonly used clinically to deliver therapeutics to intraabdominal organs (3335). We saw robust mRNA delivery for all administration routes, with IV delivery eliciting the highest placental delivery, followed by IP and IM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to IV delivery, we considered other clinically relevant delivery routes, including intramuscular (IM) and intraperitoneal (IP) administration. Intramuscular injections are the preferred route for prophylactic RNA vaccines (29, 30), including the SARS-CoV-2 vaccines (31, 32), while intraperitoneal injections are commonly used clinically to deliver therapeutics to intraabdominal organs (3335). We saw robust mRNA delivery for all administration routes, with IV delivery eliciting the highest placental delivery, followed by IP and IM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was demonstrated that lipid nanoparticles can efficiently and specifically deliver mRNA to the pancreas. [90] Nawaz et al further found that when delivering VEGF-A mRNA via LNPs, part of the internalized mRNA continued to function through EV secretion, and at the same VEGF-A protein content, different cell-secreted EVs had different degrees of effect. [91] In general, LNPs and EVs can be interconnected, and after the delivery of therapeutic molecules by LNPs, the EVs secreted by cells contain more molecules with similar biological functions in addition to therapeutic molecules, so EVs can be regarded as the functional expansion of LNPs.…”
Section: Delivery Of Nucleic Acidmentioning
confidence: 99%
“…Qiaobing Xu’s team has identified an endogenously lymph node-directing lipid nanoparticle system . Kathryn A. Whitehead’s team devised a strategy of delivering cationic helper lipid-containing lipid nanoparticles by intraperitoneal administration to deliver mRNA to pancreas, especially the insulin-producing cells . Gaurav Sahay’s lab has developed a LNP system with increased polyethylene glycol (PEG) and inclusion of a cholesterol analog, β-sitolsterol to optimize the delivery of the nebulized, LNP-based mRNA for fibrosis transmembrane conductance regulator (CFTR) protein as potential inhalable LNP-based mRNA therapies …”
Section: Outlook and Perspectivesmentioning
confidence: 99%